Perencanaan Strategis Sistem Informasi pada Balai Wilayah Sungai Maluku Menggunakan Ward and Peppard - Magdalena Alan Bungyanan; Melkior N. N. Sitokdana; Amtai Alaslan (LPPM Institut Pendidikan Nusantara Global, 2026)
The Maluku River Organisation (BWS) is a technical implementation unit (UPT) under the Directorate of Water Resources, Ministry of Public Works and Housing, that is responsible for water resources management. The main issues of BWS are the absence of an independently managed information system, so that it depends on the central government system and still uses manual processes. This research aims to create a strategic IS/IT plan aligned with the organization’s business processes to support digital transformation processes and improve organizational performance. This research adopts the Ward and Peppard methodology by using the SWOT framework, value chain, PEST frameworks, as well as portfolio mapping using the McFarlan Strategic Grid to formulate IS/IT strategies and a phased three-year implementation plan. This planning results in recommendations for developing internal IS/IT systems: SISMONIK, SILAP, SI BWS Maluku, a Mobile reporting application, and an early warning system (IoT-based) to support, manage, and optimize the technology support system for processes. The proposed implementation plan can be a guideline to reduce dependency on the central system, improve work efficiency, and support more responsive water resources management in Maluku.